In my dreams I hold a knife : a novel - Winstead, Ashley (Sourcebooks Landmark, 2022)
"Ten years after graduation, Jessica Miller has planned her triumphant return to her southern, elite Duquette University, down to the envious whispers that are sure to follow in her wake. Everyone is going to see the girl she wants them to see―confident, beautiful, indifferent. Not the girl she was when she left campus, back when Heather Shelby's murder fractured everything, including the tight bond linking the six friends she'd been closest to since freshman year. But not everyone is ready to move on. Not everyone left Duquette ten years ago, and not everyone can let Heather's murder go unsolved. Someone is determined to trap the real killer, to make the guilty pay. When the six friends are reunited, they will be forced to confront what happened that night―and the years' worth of secrets each of them would do anything to keep hidden."--Amazon.com.